Case Report: Laparoscopic Management of an Ectopic Pregnancy in a Rudimentary Non-communicating Uterine Horn - Chatziioannidou, Kyriaki; Fehlmann, Aurore; Dubuisson, Jean (Frontiers in Surgery, 2020)
Introduction Ectopic pregnancy in a non-communicating rudimentary uterine horn is a rare gynecological condition associated with a high risk of uterine rupture and important maternal mortality and morbidity. A surgical excision of the rudimentary horn is the standard treatment, usually performed by laparotomy in the second trimester. Methods A 36-year-old woman, secundigravida and nulliparous, was admitted to the emergency obstetric unit with acute pelvic pain. The ultrasound found an ectopic pregnancy at fifteen weeks gestational age with fetal cardiac activity. As her hemodynamic status was stable, a diagnostic laparoscopy was performed and confirmed the development of the pregnancy in a left rudimentary uterine horn. Results We report a total laparoscopic removal of a pre-ruptured rudimentary uterine horn containing a second trimester ectopic pregnancy, using a vessel-sealer device. To our knowledge, only three other cases of successful laparoscopic treatment of second trimester rudimentary horn pregnancies have been reported in the literature. Conclusion Laparoscopy is an efficient and safe surgical option for treating rudimentary horn second trimester pregnancy in patients with hemodynamic stability.